1997
DOI: 10.1007/s003300050102
|View full text |Cite
|
Sign up to set email alerts
|

Comparision between transrectal ultrasonography and computed tomography with rectal inflation of gas in preoperative staging of lower rectal cancer

Abstract: Computed tomography with rectal air insufflation was compared with transrectal ultrasonography (TRUS) in 63 patients. The CT protocol involved pre- and postcontrast scans with 5 mm slice thickness following air insufflation in IV antiperistaltic agent. Of the patients, 79 % were scanned in the prone position. Results of the preoperative examinations were compared with the histological findings. The CT examination had an accuracy rate of 74 %, predicting perirectal spread with a sensitivity of 83 % and a specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0
2

Year Published

1999
1999
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 18 publications
1
9
0
2
Order By: Relevance
“…Several previous studies have demonstrated that TRUS is more accurate than CT in assessing preoperative local staging of rectal cancer [7,18]. In a recent large multicenter study comparing CT and MR, better prediction of transmural tumour penetration was found by CT than by MR (accuracy 74 vs 58 %) [22]; however, it was suggested that recent developments in MR could affect these results.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Several previous studies have demonstrated that TRUS is more accurate than CT in assessing preoperative local staging of rectal cancer [7,18]. In a recent large multicenter study comparing CT and MR, better prediction of transmural tumour penetration was found by CT than by MR (accuracy 74 vs 58 %) [22]; however, it was suggested that recent developments in MR could affect these results.…”
Section: Discussionmentioning
confidence: 95%
“…In rectal cancer staging, both transrectal ultrasonography (TRUS), CT and MR imaging have all been evaluated for assessing both tumour infiltration in the bowel wall and loco-regional lymph node metastases [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21]. Despite initial promising results and subsequent technical developments of the methods, the overall results in large series of patients indicate that presently routine staging of rectal cancer cannot be justified, because the accuracy to predict tumour penetration and lymph node metastases is limited [22,23,24,25].…”
Section: Introductionmentioning
confidence: 97%
“…Endorectal ultrasound and CT scan represent the main imaging methods for prediction [4,13]. Endorectal ultrasound has been proved superior to CT scan in the evaluation of local tumor progression [12,25]. By the use of endorectal ultrasound, the T-category can be predicted with up to 90% accuracy, whereas correct predictions with CT scan reach only 70% accuracy [12,25].…”
Section: Discussionmentioning
confidence: 99%
“…Zahlreiche Untersuchungen zeigten, dass die rES als dynamische Untersuchungsmethode bei der Beurteilung der Infiltrationstiefe (uT), insbesondere bei uT1-Malignomen, und des lokoregionalen Nodalstatus (uN) der CT-Diagnostik überlegen ist [38,41,63,67,68,70,76]. Gemeinsam mit der präoperativen Biopsathistologie beeinflusst die rES maßgeblich das therapeutisch-chirurgische Vorgehen [2,45,65].…”
unclassified